EFL Teachers’ Burnout: Do Mobile Teaching Affordances Matter? - Hedayati-Kakhki, Mahnaz; Tabatabaee-Yazdi, Mona (Innovare Journal of Education, 2023)
In recent years, integrating mobile devices and network technologies has been a critical issue in the teaching and learning process, especially within the scope of English teaching and learning. The importance of technology integration in the learning and teaching process by teachers can only be deemed effective if users can realize the intended affordances in the teaching. Teachers’ affordances, accordingly, can be defined as the relationship between the properties of an educational intervention and the characteristics of the learner that enable particular kinds of learning by individuals. On the other hand, one of the critical core barriers that EFL teachers encounter in their job is the issue of burnout. Thus, because of the increased attention to the capabilities and affordances of mobile usage among teachers, this study intended to examine the relationship between EFL teachers’ mobile affordances and their burnout as its main focus. The study also aimed at determining whether gender differences influence the teachers` mobile affordances and their burnout. To this aim, 228 EFL teachers were invited to participate in this study. Data were gathered using Mobile Teaching Affordances and Maslach Burnout Inventory, and processed, analyzed, and reported using Pearson product-moment correlations and independent samples t-test. Findings proposed teachers` perceptions of mobile affordances and their burnout had significantly and negatively correlated. Furthermore, the results indicated that there was not a significant difference between males' and females` mobile affordances, however, there was a significant difference between males and females in burnout scores favoring males.